Dual epigenetic agents plus rituximab–gemcitabine–oxaliplatin as salvage treatment in relapsed/refractory diffuse large B‐cell lymphoma patients failure of salvage chemotherapy. Issue 5 (12th August 2022) - Qu, Changju; Ping, Nana; Kong, Danqing; Liu, Aining; Liu, Hailing; Xu, Ting; Xia, Fan; Wu, Depei; Jin, Zhengming
Abstract: Refractory/relapsed (R/R) diffuse large B‐cell lymphoma (DLBCL) patients' failure of salvage chemotherapy had extremely worse prognoses. Herein, 14 R/R DLBCL patients failed to salvage chemotherapy were exposed to dual epigenetic agents (Chidamide 30 mg biw*2w and Decitabine 10 mg/m 2 qd*d1–d5) and sequential R‐GemOx (rituximab 375 mg/m 2 qd d6; gemcitabine 1 g/m 2 d7, d14; and oxaliplatin 100 mg/m 2 d7) for further salvage chemotherapy. Finally, 11/14(78.6%) patients achieved overall response with 6/14(42.9%) achieving complete remission and 2‐year overall survival (OS)/progression free survival (PFS) rate was 42.7%, extremely higher than reported previously. Further subgroup analysis demonstrated that 2‐year OS/PFS rate was significantly higher in patients achieved complete/partial remission or with low international prognosis index (IPI 0–2) than that in patients with steady disease or high IPI (3–5). Common grade 3–4 adverse events were hematological toxicities. All toxicities were transient and reversible. Our report implicates that combination of dual epigenetic agents and R‐GemOx is a safe and promising alternative for R/R DLBCL patients.